Pedagogy in Artificial Intelligence: Optimizing Chatbots in the Learning of Indonesian Language and Literature - Kusuma Wardani, Diah Octavia; Gani Patindra (Expert Net: Exploration Journal of Technological Education Trends, 2025)
The influence of technology has impacted many aspects, including education, thus this acculturation needs to be carefully considered by educators in its implementation to ensure it aligns with the true direction of education. The purpose of this study is to review the optimal teaching art of the pedagogical nature of Indonesian language and literature learning by utilizing Artificial Intelligence-based chatbots. This research uses a systematic literature review model from accredited articles within the last five (5) years on the raised issue. The results of this study indicate that the AI and chatbots' ability to understand relatively natural language can be utilized as one of the instruments in Indonesian language and literature learning. A teacher must be able to embrace dimensions by being directly involved in content learning, cognitive engagement, encouraging proper and effective interaction and dialogue with chatbots, as well as providing feedback and support. Additionally, by considering both the positive and negative impacts of utilizing AI, teachers are also required to become professionals with skills in teacher training when using AI in learning. This signifies that the existence of teachers still holds educational value, even though with AI, it only serves as a supplementary teacher whose existence cannot replace the position of the original wise educator.